EXPERIENCE OF ADVANCED COUNTRIES IN DEVELOPING THE INVESTMENT ACTIVITIES OF COMMERCIAL BANKS BASED ON STOCK MARKET MECHANISMS (World Bulletin of Management and Law, 2026)
This article explores the strategic importance of integrating stock market mechanisms into the investment activities of commercial banks, particularly within the context of Uzbekistan’s evolving financial landscape. As the banking sector undergoes a transition from traditional credit-oriented models to universal banking, leveraging capital market instruments becomes essential for financial stability and economic growth. The study conducts a comparative analysis of global banking models, specifically examining the “Anglosaxon” (US/UK) and “Continental” (Germany/Japan) models, to identify best practices in portfolio diversification and risk management. Statistical analysis reveals a significant gap between developed markets, where securities comprise approximately 25-32% of bank assets, and Uzbekistan, where this figure remains at a modest 6.5%. The findings suggest that the low involvement of national banks in the stock market limits their profitability and increases credit risk exposure. The article proposes a strategic roadmap for enhancing the investment role of banks, including the implementation of asset securitization, the development of investment banking units, and the integration of digital investment platforms. Ultimately, the study concludes that fostering a robust synergy between banks and the stock market is a key driver for achieving the objectives of the “Uzbekistan — 2030” strategy and ensuring long-term institutional resilience.